2018
DOI: 10.5267/j.msl.2018.1.001
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the role of unified theory of acceptance and use of technology (UTAUT) in internet banking adoption context

Abstract: Several studies have made known that internet banking (IB) implementation is not only advantageous for banks, but also by perception and experience of IB users. Therefore, little is known about factors propelling user's intention to adopt internet banking in Pakistan. Thus, the purpose of this research is to investigate the role of unified theory of acceptance and use of technology (UTAUT) in internet banking adoption context. A quantitative approach based survey was conducted to collect the data from 398 inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
106
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(117 citation statements)
references
References 35 publications
9
106
1
1
Order By: Relevance
“…Perceived usefulness is "the degree to which a person thinks it could increase his job effectiveness using a certain program" (Davis et al, 1989). Rahi, Ghani, Alnaser, and Ngah (2018) argued that performance expectancy was one of the most significant factors amongst other variables to forecast the intention of user's internet banking adoption. Nonetheless, Early studies by Davis (1985), showed that TAM was imperfect as it did not take into account social influence to adopt and use of new information technology.…”
Section: Perceived Usefulnessmentioning
confidence: 99%
“…Perceived usefulness is "the degree to which a person thinks it could increase his job effectiveness using a certain program" (Davis et al, 1989). Rahi, Ghani, Alnaser, and Ngah (2018) argued that performance expectancy was one of the most significant factors amongst other variables to forecast the intention of user's internet banking adoption. Nonetheless, Early studies by Davis (1985), showed that TAM was imperfect as it did not take into account social influence to adopt and use of new information technology.…”
Section: Perceived Usefulnessmentioning
confidence: 99%
“…The modern studies which were concerned with user tools selection, adoption intention, and acceptance of technology were conducted from a particular angle such as: sector/ industry, tool, and user category. (Rahi et al 2018a) is one of the most recent studies that has been concerned with the impact of UTAUT on particular sector/ industry. (Rahi et al 2018a) examined the UTAUT role in the internet banking adoption context.…”
Section: Literature Review User Tool Selection Technol-ogy Usementioning
confidence: 99%
“…(Rahi et al 2018a) is one of the most recent studies that has been concerned with the impact of UTAUT on particular sector/ industry. (Rahi et al 2018a) examined the UTAUT role in the internet banking adoption context. The individuals' intention as critical factors have been studied by Karahoca et al (2018).…”
Section: Literature Review User Tool Selection Technol-ogy Usementioning
confidence: 99%
See 1 more Smart Citation
“…In 2017, the budget increased to 45 milyar Rupiah and expected tourist arrivals is above 1 million people (BPS, 2016). However, based on the data from Badan Pusat Statistik Provinsi Sumatera Utara, the number of foreign tourists who entered through three entrances until 2015 reached 229,288 people down 5.18% compared with 2012 (BPS, 2016;Rahi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%